PEMANFAATAN LIMBAH PADAT KELAPA SAWIT DI PTPN X - Ar Rum Nur Fachira, Alya Suwayya, Khairunnisa Gultom, Mutiara Faizah, Putri Syahrani, Zuhrina Aidha (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Background: The oil palm is the superior commodity of Indonesia, which plays an important role to produce crude palm oil or crude plam oil (CPO) and palm oil or palm oil (KPNO) pilgrimated obtained based on the processing of fresh fruit bunnch (TBS) of oil palm. In addition to increased production and the projection of the palm industrial market, the palm plant factory resulted in a problem of the increase of waste volume. Judging from the Joint Data Organizer of Indonesian Palm Older Business Own Indonesia, Indonesia's palm oil production amounted to 4.95 million tons in October 2023. The number rose 9.17% compared to a month before 44 million tons. Objective: This study aims to regulate the benefits of solid waste and wastewater liquid in PTPN X. Research method; The method is descriptive research using qualitative method. Information is obtained by informants, including 2 major informants and 2 person's informants. Dara is collected based on further interviews, observation and document review. Conclusion: The results showed on this PKS there were several solid waste which was produced from the process of oil palm oil management. Where, the company in its operation produces solid waste in the form of fiber, shell, empty bandage, solid and ash boiler.